(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper is devoted to presenting a new mathematical development and hardware implementation of an accurate and stable technique for the current estimation-based sliding mode observer in high-performance speed-sensorless ac-drive. The proposed algorithm is built by using induction motor (IM) flux equations in two referential frames to enhance the robustness of the observer. Indeed, all equations are given in both stator-flux and rotor-flux rotating frames. On the other hand, to eliminate the necessity of rotor-speed adaptation, a fully speed-sensorless scheme is adopted. Furthermore, to minimize chattering and improve accuracy, a new fuzzy sliding surface is introduced instead of the conventional correction vector. The observer stability is guaranteed by means of Lyapunov’s second method. The feasibility and the effectiveness of the proposed algorithm are verified by using a hardware setup based on the DS1104 controller board. Experimental results are shown and discussed.